Phenotypic alterations of neuropeptide Y and calcitonin gene-related peptide-containing neurons innervating the rat temporomandibular joint during carrageenan-induced arthritis - Damico, J.P. (PAGEPress Publications, 2012)
The aim of this study was to identify immunoreactive neuropeptide Y (NPY) and calcitonin gene-related peptide (CGRP) neurons in the autonomic and sensory ganglia, specifically neurons that innervate the rat temporomandibular joint (TMJ). A possible variation between the percentages of these neurons in acute and chronic phases of carrageenan-induced arthritis was examined. Retrograde neuronal tracing was combined with indirect immunofluorescence to identify NPY-immunoreactive (NPY-IR) and CGRP- immunoreactive (CGRP-IR) neurons that send nerve fibers to the normal and arthritic temporomandibular joint. In normal joints, NPY-IR neurons constitute 78±3%, 77±6% and 10±4% of double-labeled nucleated neuronal profile originated from the superior cervical, stellate and otic ganglia, respectively. These percentages in the sympathetic ganglia were significantly decreased in acute (58±2% for superior cervical ganglion and 58±8% for stellate ganglion) and chronic (60±2% for superior cervical ganglion and 59±15% for stellate ganglion) phases of arthritis, while in the otic ganglion these percentages were significantly increased to 19±5% and 13±3%, respectively. In the trigeminal ganglion, CGRP-IR neurons innervating the joint significantly increased from 31±3% in normal animals to 54±2% and 49±3% in the acute and chronic phases of arthritis, respectively. It can be concluded that NPY neurons that send nerve fibers to the rat temporomandibular joint are located mainly in the superior cervical, stellate and otic ganglia. Acute and chronic phases of carrageenan-induced arthritis lead to an increase in the percentage of NPY-IR parasympathetic and CGRP-IR sensory neurons and to a decrease in the percentage of NPY-IR sympathetic neurons related to TMJ innervation.